Efficient resolution of racemic crown-shaped cyclotriveratrylene derivatives and isolation and characterization of the intermediate saddle isomer - Götz, Sven; Schneider, Andreas; Lützen, Arne (Beilstein Journal of Organic Chemistry, 2019)
The preparative resolution of a trifunctionalized C3-symmetrical chiral cyclotriveratrylene derivative was achieved via high-performance liquid chromatography (HPLC) on a chiral stationary phase. This approach is a promising alternative to the previously reported resolution through formation of diastereomeric esters because it involves fewer synthetic steps and is less prone to thermal (re)racemization. During these studies an intermediate saddle conformer could also be isolated and characterized by 1H and 13C NMR spectroscopy. The HPLC separation method was further developed in order to allow investigations on the racemization behavior of the cyclotriveratrylene derivative.
Keywords: chiral resolution; cyclotriveratrylenes; HPLC; macrocycles; racemization; saddle isomer